STUDENTS’ LIVED EXPERIENCES PRACTICING DIGITAL LITERACY USING YOUTUBE AS AN ENGLISH LEARNING TOOL - Kriswinahyu , Aprilia Dyah; Kastuhandani, Fidelis Chosa (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2024)
Technology integration transformed English learning, innovating tools and platforms that change educational dynamics. Among various digital platforms, YouTube emerges as a versatile global resource with extensive content for English learning. However, simply providing access to YouTube does not guarantee effective, safe use or learning. This phenomenological study explores the lived experiences of students in the English Language Education Study Program at Sanata Dharma University using YouTube to learn English. Students' lived experiences shown through their beliefs, feelings, actions, and decision-making on YouTube. This research examined how students practice digital literacy while learning English on YouTube and how these practices give meaning to their learning. Findings revealed experiences like evaluating video trustworthiness, collaborating with fellow YouTubers, creating videos, addressing safety and privacy concerns, and applying videos creatively for personalized language goals significantly impacted their learning. Students expressed positive attitudes about these digital literacy practices, emphasizing the benefits of self-paced access to authentic English resources. This study provides insight into how students leverage digital platforms like YouTube for language learning through critical digital literacy practices. The findings suggest implications for educators seeking to train students in determining credible information for learning through digital platforms, as this issue gained substansial participants’ attention.